Shortage of essential antimicrobials: a major challenge to global health security. Issue 11 (2nd November 2021) - Shafiq, Nusrat; Pandey, Avaneesh Kumar; Malhotra, Samir; Holmes, Alison; Mendelson, Marc; Malpani, Rohit; Balasegaram, Manica; Charani, Esmita
Abstract : The lack of access to safe and effective antimicrobials for human populations is a threat to global health security and a contributor to the emergence and spread of antimicrobial resistance (AMR). The increasingly common shortages of antimicrobials are an additional threat to the emergence of AMR. While the threat of such drug shortages is most acutely experienced in low-income and middle-income settings, their consequences impact the quality and effectiveness of antimicrobials worldwide. Furthermore, there is a need for robustly conducted studies examining the impact of these increasingly prevalent shortages on patient outcomes and on the emergence and spread of AMR. In this review, we have mapped common drivers for antimicrobial shortages and propose strategies for rethinking the regulation, supply and pricing of antimicrobials to secure their sustainable access across diverse healthcare systems and to help minimise the unintended consequences of weak and ineffective supply chains. Greater government involvement in antimicrobial manufacture and supply is essential to ensure no one is left behind. Dedicated demand systems need to be developed for antimicrobials which take into consideration evolving AMR patterns, burden of diseases, pandemic events and supply and demand issues and facilitate implementation of strategies to address them. Interventions, ranging from advocacy and forecasting to public–private collaborations, new economic models and international consortia working across countries and supply chains, will help assure access to safe and effective antimicrobials to all populations around the globe and ensure that shortages no longer contribute to AMR.